BERD Platform: The Journey from User Needs to Agile Development - Hassan, Mahmoud (Electronic Communications of the EASST, 2025)
With the movement of the Open Science initiatives, a research data infrastructure where an integrated management of (un)structured data and associated scientific software in science, economics and business is highly desired by researchers, libraries and institutes which is inline with open software and standards and aligned with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). The BERD@NFDI consortium aims to establish a research data management platform for Business, Economics, and Related Data (BERD) within the German National Research Data Infrastructure (NFDI). The platform will host diverse resources, such as research data from areas like marketing, analytics, and social sciences, involving various partner institutions and user communities. This results in an agile, user- driven requirements engineering process. In this paper, I present the steps we took in our Software Development Team (SDT) from gathering community requirements through formalizing these requirements to the agile software engineering process of building the BERD platform. An evaluation of the different evolving measures and practices taken for the development of the platform will be discussed.